2023
DOI: 10.3389/fimmu.2023.1104828
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19, tuberculosis and HIV/AIDS: Ménage à Trois

Abstract: In December 2019, a novel pneumonic condition, Coronavirus disease 2019 (COVID- 19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), broke out in China and spread globally. The presentation of COVID-19 is more severe in persons with underlying medical conditions such as Tuberculosis (TB), Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) and other pneumonic conditions. All three diseases are of global concern and can significantly affect the lungs with characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…Additionally, disparities persist along ethnic lines, with AIDS rates among blacks and African Americans eight times higher than among whites 20 . Similarly, data from South Africa reflect the impact of COVID-19 on HIV, evidenced by reduced testing, including for tuberculosis 4,6,8,44 . These findings highlight the importance of considering socioeconomic disparities in regional HIV/AIDS control efforts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, disparities persist along ethnic lines, with AIDS rates among blacks and African Americans eight times higher than among whites 20 . Similarly, data from South Africa reflect the impact of COVID-19 on HIV, evidenced by reduced testing, including for tuberculosis 4,6,8,44 . These findings highlight the importance of considering socioeconomic disparities in regional HIV/AIDS control efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some contradictory data, it is evident that SARS-CoV-2 has had a detrimental impact on people living with HIV. Previous studies have shown that comorbidities increase the risk of severe clinical forms of COVID-19, including immunosuppression, cardiovascular disease, cancer, and tuberculosis 20,44,45 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with pulmonary tuberculosis and HIV/AIDS might exhibit heightened susceptibility to SARS-CoV-2 infection, potentially resulting in lethal synergistic effects and increased disease severity [21]. Moreover, worldwide, it is estimated that between 10 to 25% of TB infections occur extrapulmonarily, infecting virtually any organ, thus definitive diagnosis usually requires invasive procedures and complex imaging examinations, as symptoms can be very heterogeneous [22].…”
Section: Introductionmentioning
confidence: 99%
“…Tuberculosis, caused by Mycobacterium tuberculosis (Mtb), remains one of the deadliest infectious diseases in the world, and the co-infections of tuberculosis with COVID-19 and HIV have become a matter of global concern ( 1 , 2 ). The Mtb is a well-equipped pathogen that poses a significant risk to human health, as it possesses inherent capabilities to adapt and reside within the phagosomes of human macrophage, persisting for several years, or even decades within specific granulomas ( 3 ).…”
mentioning
confidence: 99%